Research progress on the protective effects of aucubin in neurological diseases - Ping Yang; Qiaoyue Zhang; Hengyan Shen; Xinyu Bai; Ping Liu; Tao Zhang (Taylor & Francis Group, 2022)
Context Aucubin (AU), an iridoid glycoside that is one of the active constituents of Eucommia ulmoides Oliv. (EUO) (Eucommiaceae), a traditional Chinese medicine, has been extensively studied in the management of neurological diseases (NDs). However, a comprehensive review of its effects and mechanisms in this regard is currently not available.Objective To compile the protective effects and mechanisms of AU in NDs and provide a basis for further research.Methods We used 'aucubin' as the 'All Fields' or 'MeSH' in PubMed, Web of Science and China National Knowledge Infrastructure without any limitation to search all relevant articles as comprehensively as possible; we selected the articles on AU treatment of NDs for summary.Results Studies reviewed herein reported that AU improved the symptoms or prognosis of Parkinson's disease, Alzheimer's disease, intracerebral haemorrhage, diabetic encephalopathy, epilepsy, anxiety and depression, and traumatic brain injury. The pharmacological mechanisms involved in repairing neuronal loss were postulated to include increasing γ-aminobutyric acid (GABA) content in the synapse, promoting differentiation of neural precursor cells into GABAergic neurons, providing antioxidant and anti-neuroinflammation activities, as well as enhancing autophagy and anti-apoptotic actions.Discussion and conclusions The protective effects of AU on some NDs have been confirmed. According to the pharmacological effects, AU is also highly likely to have protective effects on other NDs, which can be realized by further in vivo and in vitro basic research, and clinical trials. In the future, AU may be used for clinical prevention or treatment of patients with neurological diseases.